Urban waterlogging risk assessment based on internet open data: A case study in China. (January 2018) - Lin, Tao; Liu, Xiaofang; Song, Jinchao; Zhang, Guoqin; Jia, Yuqiu; Tu, Zhezhi; Zheng, Zehua; Liu, Chaolun
Abstract: Urban waterlogging caused by rainstorm occurred frequently in many cities of China these years and seriously influenced city safety and residents' daily life. Meanwhile, many remarkable achievements with open data and big data have been applied in urban research, but rare to urban waterlogging research. Taking Xiamen city in China as a case, this study aims to analyze spatial-temporal distribution of waterlogging and assess waterlogging risk of each district in the city. Risk assessment model was built by considering both population and urban public facilities, which acquired from coupling urban internet open data and field investigation. Then we analyzed the government management efficiency through comparison of urban government management plan and waterlogging information from internet. The result indicates that internet open data can be utilized as an effective tool to identify urban waterlogging risk in China, to verify urban waterlogging management efficiency, and to support for urban waterlogging risk prevention and management combining with field investigation. Highlights: Internet open data can be used to identify urban waterlogging risk. Internet open data is effective to verify urban waterlogging management efficiency. Internet open data should be coupled with field investigation for better research.